2016
DOI: 10.3138/ptc.2015-50
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Reduced Perceived Access to Physiotherapy Services among People with Low Back Disorders

Abstract: Purpose: To explore which socio-demographic, clinical, and other factors are associated with reduced perceived access to physiotherapy among people with low back disorders. Methods: A cross-sectional study design was used to evaluate perceived access to physiotherapy services in a convenience sample of 111 people with low back disorders presenting to a spinal triage service. Participants were asked whether they felt that they had reduced access to physiotherapy as a result of cost, wait time, or location. Biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Major constraints to obtaining Physiotherapy in the study setting include travel cost, time and work commitment and lack of resources/facilities for Physiotherapy. These constraints were similar to what authors of previous studies had noted [4, 16, 20, 39]. In line with the finding of this study, a predictive model confirms that individuals who agreed that they had difficulty in getting to where physiotherapy was available were seven times more likely to utilize physiotherapy service.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Major constraints to obtaining Physiotherapy in the study setting include travel cost, time and work commitment and lack of resources/facilities for Physiotherapy. These constraints were similar to what authors of previous studies had noted [4, 16, 20, 39]. In line with the finding of this study, a predictive model confirms that individuals who agreed that they had difficulty in getting to where physiotherapy was available were seven times more likely to utilize physiotherapy service.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, determinants of utilization and supply of Physiotherapy services are multifarious and widely varied in different countries [ 15 ]. Some of these factors are aging workforce and attrition [ 13 ], lack or poor remuneration and recognition, workforce shortages, dearth of locum opportunities and rural-urban related factors [ 14 ], cost, waiting time, location [ 16 ], travel burden, flexibility in work hours, professional support and development, as well as autonomy of practice [ 17 ]. Other factors include insurmountable workloads, limited access to continuous professional development and narrow opportunity for career progression, non-availability of employment openings for partners, perceived scarcity of quality secondary schools, and intention to travel [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This helps to reduce inequity of access to physiotherapy care for people with knee OA, which may arise from geographical location or socioeconomic status. 33 Indeed, a community-based survey of 1000 people with arthritis in Australia found that over two-thirds of respondents felt that they did not cope well with their condition because of the healthcare they experienced, and felt that they had poor access to medical doctors, specialists and allied health professionals. 34 Allowing patients the flexibility to choose which type of physiotherapy service best suits their needs, preferences and financial situation also aligns with a philosophy of patient-centred care, 35 36 and permits the patient to have some control over their own healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple barriers to people engaging in a healthcare service, which includes physiotherapy following ACL injury/ surgery (Carrillo et al, 2011). Patient-specific barriers include health literacy/understanding of the condition, cultural beliefs and socio-economic status; provider-specific barriers include clinician skills/knowledge and patient interactions; healthcare system barriers include cost, accessibility/waiting times, location of services and the involvement of multiple providers (Bath et al, 2016;Douthit, Kiv, Dwolatzky, & Biswas, 2015;Scheppers, Van Dongen, Dekker, Geertzen, & Dekker, 2006). In New Zealand, barriers to engaging with primary healthcare services include location, cost, suitability and awareness of services (Ministry of Health, 2001).…”
Section: Duration and Quantity Of Physiotherapy Treatmentmentioning
confidence: 99%